Escolha de cursos superiores por alunos de uma cooperativa de ensino na região do Médio Araguaia (Barra do Garças, MT) - Silva, Eliel Ferreira da (2006)
The objective of the research was to identify the criteria considered relevant by third – year student of a cooperative secondary school in Barra do Garças – MT of Brazil regarding their professional choices. Based on the vocational theory of Bohoslavsky, the principal external and internal factors that could influence the professional orientation were gathered. The methodology used looked to investigate the socio – economic profile of the families of twenty eight third year students of the are COOPEMA (Coopertiva de Ensino do Médio Araguaia) in 2005. Then the next year, the students were interviewed while attending their fist year of university in the central west region of Brazil. During this second phase, individual semi directed interview were done with fourteen student already attending university in the region between the month of January and March of 2006. The results show that the fact that these students attended a cooperative secondary school does not influence significantly their professional orientation. Rather, the principles off the university shidy were determined by the students’ antecedents their family life trajectory and their relation with their pairs. The ancture of the cooperative school helped as an extra reinforcement of those choices.